Development of Uniform Porous Carbons From Polycarbazole Phthalonitriles as Durable CO2 Adsorbent and Supercapacitor Electrodes - Alenezi, Ghadeer Thani; Rajendran, Narendran; Abdel Nazeer, Ahmed; Makhseed, Saad (Frontiers in Chemistry, 2022)
Advances in new porous materials have recognized great consideration in CO2 capture and electrochemical energy storage (EES) applications. In this study, we reported a synthesis of two nitrogen-enriched KOH-activated porous carbons prepared from polycarbazole phthalonitrile networks through direct pyrolysis protocol. The highest specific surface area of the carbon material prepared by pyrolysis of p-4CzPN polymer reaches 1,279 m2 g−1. Due to the highly rigid and reticular structure of the precursor, the obtained c-4CzPN–KOH carbon material exhibits high surface area, uniform porosity, and shows excellent CO2 capture performance of 19.5 wt% at 0°C. Moreover, the attained porous carbon c-4CzPN–KOH showed high energy storage capacities of up to 451 F g−1 in aqueous electrolytes containing 6.0 M KOH at a current density of 1 A g-1. The prepared carbon material also exhibits excellent charge/discharge cycle stability and retains 95.9% capacity after 2000 cycles, indicating promising electrode materials for supercapacitors.